Stimulating scientific minds among early secondary students in Malaysia: a pilot study using ‘engineering and electronics made fun’ approach - Ab Razak, Mohd Zulhakimi; Ahmad Fuad, Fazia Adyani; Abdullah, Azlina; Mohd Nood, Mansor (2019)
This paper discusses the development of scientific thinking at an early stage of secondary education in Malaysia. Since the engineering aspects were introduced using ‘Electronics Made Fun’ approach, this pilot study was targeted at the first stage of secondary education. This is because at this stage, the students show signs of maturity in thinking and would be able to understand the concept of science and engineering at a greater extent. This study was conducted on 36 Form 1 students from Sekolah Menengah Agama Nilai, which the genders were divided equally. The aims of the study are to introduce electronics engineering in a fun and easy-to-understand concept, and to bridge the gap between universities and schools in Malaysia. This study was conducted in three stages: 1) Educating the students using information and notes, 2) Practical aspects of the study, where the students were given hands-on experiences using electronics kits and components, and 3) Implementation of knowledge and skills through group projects. Before the study was conducted, only 16.7% of the students can define proper concept of science and engineering, whereas only 19.4% of them were familiar with electronics components. After five weeks of regular meetings and activities with 34 contact hours, almost 94.4% of the students responded well in defining science and engineering. Interestingly, as much as 91.7% of them would like to attend such programme again in the future. This pilot study has paved the path towards empowering STEM and developing scientific minds at early stage of education in Malaysia.